Comparative Analysis of the Structure and Function of AAA+ Motors ClpA, ClpB, and Hsp104: Common Threads and Disparate Functions - Duran, Elizabeth C. (Front Mol Biosci, 2017)
Cellular proteostasis involves not only the expression of proteins in response to environmental needs, but also the timely repair or removal of damaged or unneeded proteins. AAA+ motor proteins are critically involved in these pathways. Here, we review the structure and function of AAA+ proteins ClpA, ClpB, and Hsp104. ClpB and Hsp104 rescue damaged proteins from toxic aggregates and do not partner with any protease. ClpA functions as the regulatory component of the ATP dependent protease complex ClpAP, and also remodels inactive RepA dimers into active monomers in the absence of the protease. Because ClpA functions both with and without a proteolytic component, it is an ideal system for developing strategies that address one of the major challenges in the study of protein remodeling machines: how do we observe a reaction in which the substrate protein does not undergo covalent modification? Here, we review experimental designs developed for the examination of polypeptide translocation catalyzed by the AAA+ motors in the absence of proteolytic degradation. We propose that transient state kinetic methods are essential for the examination of elementary kinetic mechanisms of these motor proteins. Furthermore, rigorous kinetic analysis must also account for the thermodynamic properties of these complicated systems that reside in a dynamic equilibrium of oligomeric states, including the biologically active hexamer.